2017
DOI: 10.1155/2017/2139791
|View full text |Cite
|
Sign up to set email alerts
|

Modified Approach for Optimization of Real Life Transportation Problem in Neutrosophic Environment

Abstract: To the best of our knowledge, there is only one approach for solving neutrosophic cost minimization transportation problems. Since neutrosophic transportation problems are a new area of research, other researchers may be attracted to extend this approach for solving other types of neutrosophic transportation problems like neutrosophic solid transportation problems, neutrosophic time minimization transportation problems, neutrosophic transshipment problems, and so on. However, after a deep study of the existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Furthermore, we enrich the DM-TP1 with the defuzzification score function [16] in order to convert the neutrosophic trapezoidal fuzzy parameters to crisp number. us, the score function for the neutrosophic trapezoidal fuzzy number N � 〈(N a , N b , N c , N d ); T N , I N , F N 〉 is defined by equations ( 5) and ( 6).…”
Section: The Proposed Method: Dhouib-matrix-tp1 (Dm-tp1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we enrich the DM-TP1 with the defuzzification score function [16] in order to convert the neutrosophic trapezoidal fuzzy parameters to crisp number. us, the score function for the neutrosophic trapezoidal fuzzy number N � 〈(N a , N b , N c , N d ); T N , I N , F N 〉 is defined by equations ( 5) and ( 6).…”
Section: The Proposed Method: Dhouib-matrix-tp1 (Dm-tp1)mentioning
confidence: 99%
“…Definition 4 (see [16]). For a single-valued neutrosophic number N � 〈(N a , N b , N c , N d ); T N , I N , F N 〉, its score function is defined by M(􏽥 c N ij ) as follows:…”
Section: Basic Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Srinivas and Ganesan [14] have applied branch and bound method for unraveling assignment problems. Transportation problems under neutrosophic domain were resolved by Thamaraiselvi et al [15] and Akansha Singh et al [2]. With linguistic variables, Anil and Khot [3] resolved fuzzy assignment problem through BnB method.…”
Section: Introductionmentioning
confidence: 99%
“…Later with the time some intriguing extensions of fuzzy sets were developed like-intuitionistic fuzzy set (IFS) [2], interval-valued intuitionistic fuzzy set (IVIFS) [3], Pythagorean fuzzy set (PFS) [24][25][26], interval-valued Pythagorean fuzzy set (IVPFS) [32], neutrosophic set [18][19][20], SVNS [23] and IVNS [22] etc. In this note, a deep study have been made to analyze the ranking order of some of the extensions of fuzzy sets like, IFS [8,9,30], PFS [32], IVPFS [4][5][6][7]11,12,16,17,31], SVNS [1,10,[13][14][15]21] and IVNS [10,13]. After a rigorous study it has been observed that there exist some restrictions in the existing methods [10,13] for comparing SVNS and IVNS.…”
mentioning
confidence: 99%